Skip to main content
\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)
Mathematics LibreTexts

Section 5.7 Answers

  • Page ID
    28913
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \) \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\) \(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)

    1. \(y_{p}=\frac{-\cos 3x\ln |\sec 3x+\tan 3x|}{9}\)

    2. \(y_{p}=-\frac{\sin 2x\ln |\cos 2x|}{4}+\frac{x\cos 2x}{2}\)

    3. \(y_{p} = 4e^{x} (1 + e^{x} ) \ln(1 + e^{−x} )\)

    4. \(y_{p} = 3e^{x} (\cos x \ln | \cos x| + x \sin x)\)

    5. \(y_{p}=\frac{8}{5}x^{7/2}e^{x}\)

    6. \(y_{p}=e^{x}\ln (1-e^{-2x})-e^{-x}\ln (e^{2x}-1)\)

    7. \(y_{p}=\frac{2(x^{3}-3)}{3}\)

    8. \(y_{p}=\frac{e^{2x}}{x}\)

    9. \(y_{p}=x^{1/2}e^{x}\ln x\)

    10. \(y_{p}=e^{-x(x+2)}\)

    11. \(y_{p}=-4x^{5/2}\)

    12. \(y_{p} = −2x^{2} \sin x−2x \cos x\)

    13. \(y_{p}=-\frac{xe^{-x}(x+1)}{2}\)

    14. \(y_{p}=-\frac{\sqrt{x}\cos\sqrt{x}}{2}\)

    15. \(y_{p}=\frac{3x^{4}e^{x}}{2}\)

    16. \(y_{p}=x^{a+1}\)

    17. \(y_{p}=\frac{x^{2}\sin x}{2}\)

    18. \(y_{p}=-2x^{2}\)

    19. \(y_{p}=-e^{-x}\sin x\)

    20. \(y_{p}=-\frac{\sqrt{x}}{2}\)

    21. \(y_{p}=\frac{x^{3/2}}{4}\)

    22. \(y_{p}=-3x^{2}\)

    23. \(y_{p}=\frac{x^{3}e^{x}}{2}\)

    24. \(y_{p}=-\frac{4x^{3/2}}{15}\)

    25. \(y_{p}=x^{3}e^{x}\)

    26. \(y_{p}=xe^{x}\)

    27. \(y_{p}=x^{2}\)

    28. \(y_{p} = xe^{x} (x − 2)\)

    29. \(y_{p}=\sqrt{x}e^{x}(x-1)/4\)

    30. \(y=\frac{e^{2x}(3x^{2}-2x+6)}{6}+\frac{xe^{-x}}{3}\)

    31. \(y = (x − 1)^{2} \ln(1 − x) + 2x^{2} − 5x + 3\)

    32. \(y = (x^{2}−1)e^{x}−5(x−1)\)

    33. \(y=\frac{x(x^{2}+6)}{3(x^{2}-1)}\)

    34. \(y=-\frac{x^{2}}{2}+x+\frac{1}{2x^{2}}\)

    35. \(y=\frac{x^{2}(4x+9)}{6(x+1)}\)

    38.

    1. \(y=k_{0}\cosh x+k_{1}\sinh x+\int _{0}^{x}\sinh (x-t)f(t)dt\)
    2. \(y'=k_{0}\sinh x+k_{1}\cosh x+\int _{0}^{x}\cosh (x-t)f(t)dt\)

    39. 

    1. \(y(x)=k_{0}\cos x+k_{1}\sin x+\int _{0}^{x}\sin (x-t)f(t)dt\)
    2. \(y'(x)=-k_{0}\sin x+k_{1}\cos x+\int_{0}^{x}\cos (x-t)f(t)dt\)